Factors associated with high hidden blood loss in patients undergoing primary total knee arthroplasty for osteoarthritis: a cross-sectional retrospective study of 1444 patients - Tao Deng; Yongjian Liang; Chi Xu; Libo Hao; Jun Fu; Jiying Chen (BMC Musculoskeletal Disorders)
Abstract Purpose Total knee arthroplasty (TKA) can cause significant hidden blood loss after surgery, and transfusion or erythropoietin (EPO) treatment may be required. This study aimed to identify the factors associated with blood loss in patients undergoing TKA for osteoarthritis (OA). Methods We retrospectively enrolled 1444 OA patients undergoing primary TKA from January 2022 to June 2024. The patients were divided into two groups according to the grade of hidden blood loss. To identify the key influencing factors, we conducted a logistic regression analysis. Results This study analyzed 1,444 primary arthroplasty cases, identifying 236 patients with high hidden blood loss (HHBL). Coronary artery disease (CAD) was significantly more prevalent in the HHBL group (15.3% vs. 9.4%, p = 0.006). Preoperative EPO use was higher in the low hidden blood loss (LHBL) group (21.9% vs. 9.3%, p < 0.001). Significant preoperative lab differences included hemoglobin, hematocrit, and platelet count. Surgical factors associated with HHBL included left knee TKA, conventional mechanical TKA (CMTKA), longer operation times, and intraoperative blood loss (IBL) > 20%. Postoperatively, the HHBL group had significantly more transfusions and longer hospital stays. Logistic regression identified CAD, platelet count, left knee surgery, CMTKA, operation time, and preoperative EPO use as significant factors influencing HHBL. These findings highlight the need for targeted strategies to manage blood loss in knee arthroplasty patients. Conclusions This study identifies several factors associated with high hidden blood loss in patients undergoing TKA for osteoarthritis. CAD, CMTKA, prolonged operation time, left-sided surgery, lower preoperative platelet count, and lack of preoperative erythropoietin (EPO) use were significantly linked to HHBL. While these associations highlight potential targets for intervention, further prospective studies are needed to confirm causality.